The Implications of Intelligence Practice Within and Beyond the State: An Analytical Model - Gill, Peter (Journal of Regional Security, 2018)
The study of the democratisation of intelligence in former authoritarian regimes and, more broadly, the relationship between intelligence and democracy, has hitherto concentrated on state intelligence services. The article challenges the utility of this state-centric model and considers the significance of corporate and para-state sectors of intelligence including their multiple interactions with states. ‘Securitism’ is developed as a model of these interactions which can be used in the analysis of contemporary intelligence governance and the profound challenges posed to the possibility of democratic control and oversight.